Dietary salt consumption and the knowledge, attitudes and behavior of healthy adults: a cross-sectional study from Jordan. Issue 1 (1st January 2018) - Alawwa, Izzat; Dagash, Rajaa; Saleh, Akram; Ahmad, Abdelaziz
ABSTRACT: High dietary sodium is recognized as a silent killer responsible for 2.3 million deaths worldwide in 2010 predominantly secondary to hypertension and its complications. Although high salt consumption is considered a worldwide public health problem, its magnitude is highly variable among different communities; therefore, it is important to study locally. This study aimed to evaluate habitual salt consumption, its important correlations, as well as the knowledge, attitude, and behavior of healthy Jordanian citizens. As potassium consumption is highly correlated and important we aimed to study both jointly. In this descriptive cross-sectional study we enrolled 103 healthy adult Jordanian citizens. All participants were interviewed for questionnaire filling, physical examination, and instructed on proper 24-hour urine collection procedure. We measured sodium and potassium concentration in the provided controlled 24-hour urine collection samples, as it is presently considered the gold standard for evaluating daily intake. The results showed an average sodium intake of 179 mmol (4.1 g) per day [higher in males at 186 mmol (4.3 g) vs. 173 mmol (4.0 g) for females], significantly above the current WHO recommendations, though only 8% regularly add salt to food. Ironically, most participants (82%) believe their salt consumption was appropriate and only 29% thought they may benefit from reducing salt intake. On the other hand, potassium intake is far below the current WHO recommendations. High sodium and low potassium intake have synergistic adverse effects on public health that is not currently addressed in Jordan. We conclude that Jordanian citizens currently consume high sodium and low potassium diet and are mostly unaware of its negative impact on their health. Hence, it is crucial for healthcare providers to intervene and adopt long-term strategies to control salt intake to reduce its negative effects in Jordan and elsewhere.